1999
DOI: 10.1128/jvi.73.6.4678-4688.1999
|View full text |Cite
|
Sign up to set email alerts
|

Control of Cell Cycle Entry and Apoptosis in B Lymphocytes Infected by Epstein-Barr Virus

Abstract: Infection of human B cells with Epstein-Barr virus (EBV) results in activation of the cell cycle and cell growth. To interpret the mechanisms by which EBV activates the cell, we have assayed many proteins involved in control of the G0 and G1phases of the cell cycle and regulation of apoptosis. In EBV infection most of the changes, including the early induction of cyclin D2, are dependent on expression of EBV genes, but an alteration in the E2F-4 profile was partly independent of viral gene expression, presumab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(18 citation statements)
references
References 77 publications
2
16
0
Order By: Relevance
“…However, some patterns seem to emerge as to the impact of EBV infection on cellular gene expression, which are congruent with our results. EBNA2 is the first EBV gene to be detected after infection and at 72 hr postinfection we previously measured expression of most latency‐associated EBV genes, in good agreement with that we found differential expression of validated EBNA2 targets such as CDK2, 4 and 6, and EBNA1 target genes such as BIRC5 . The fact that we find no EBNA3 or LMP1 target genes suggests that the impact of these proteins on cellular gene expression is less pronounced at 72 hr after infection.…”
Section: Discussionsupporting
confidence: 90%
“…However, some patterns seem to emerge as to the impact of EBV infection on cellular gene expression, which are congruent with our results. EBNA2 is the first EBV gene to be detected after infection and at 72 hr postinfection we previously measured expression of most latency‐associated EBV genes, in good agreement with that we found differential expression of validated EBNA2 targets such as CDK2, 4 and 6, and EBNA1 target genes such as BIRC5 . The fact that we find no EBNA3 or LMP1 target genes suggests that the impact of these proteins on cellular gene expression is less pronounced at 72 hr after infection.…”
Section: Discussionsupporting
confidence: 90%
“…Although Gutierrez et al (1999) suggested that defects in Bax might contribute to FAS resistance in BL, and we and others have identified Bax mutations in BL cell lines (Brimmell et al, 1998;Meijerink et al, 1998;Gutierrez et al, 1999), the expression of Bax and other Bcl-2 family proteins did not correlate with TRAIL sensitivity (Spender et al, 1999). Other potential mechanisms of resistance that might account for TRAIL resistance include altered expression of other regulatory molecules, such as death-associated protein 3 (DAP3) (Miyazaki & Reed, 2001).…”
Section: Discussionmentioning
confidence: 63%
“…Cell isolation, culture and infection with EBV. Primary B cells were isolated from mixed-donor platelet-depleted buffy coat residues (North London Blood Transfusion Service) by positive selection, using anti-CD19 monoclonal antibody (mAb)-coated magnetic beads (M450 pan-B Dynabeads and Detachabeads (Dynal)) as described previously (Cannell et al, 1996;Spender et al, 1999). Flow cytometric analysis was performed using fluorescein isothiocyanate (FITC)-conjugated anti-CD20 mAbs (Dako) to monitor cell purity.…”
Section: Methodsmentioning
confidence: 99%